Market competition and firm investment decisions: An empirical study of Asian economies - Alexander, Joshua Abraham; Gavriell, Kelly; Juliana, Rita (The Economics and Finance Letters, 2025)
This study examines how market competition can influence corporate investment decisions in Asian countries. Using firm-level data collected from Refinitiv from 2004 to 2023, this study analyzes the Herfindahl-Hirschman Index (HHI) as a proxy to measure market concentration and how it affects corporate investment. The results show that market concentration positively impacts corporate investments, suggesting that higher market concentration encourages investment. Monopolies or less competitive markets have greater pricing power and financial viability to sustain investments. Furthermore, the results establish that developed countries are more responsive to market concentration. Developed countries appear more responsive to market concentration due to stronger institutions, regulatory stability, and political certainty, enabling investments in infrastructure and innovation. In contrast, developing countries invest in immediate development through capital expenditure, often constrained by weaker regulatory environments and limited access to capital. This discourages innovation and long-term growth. Instead, these economies rely more on state-owned enterprises and family conglomerates that can hinder competition. This study discusses the importance of competition in stimulating corporate investments. Such insights may be useful to policymakers in determining what is required for economic growth, while also serving as valuable guidance for corporate leaders in making investment decisions across various economic and institutional environments.